Effect of pore forming agents on the properties and performance of the supported liquid membrane for levulinic acid separation - Rajendaren, Vikneswary; Syed Mohd Saufi, Tuan Chik; Mior Ahmad Khushairi, Mohd Zahari (Elsevier B.V., 2024)
The porosity of the membrane support plays a crucial role in the performance and efficiency of the supported liquid membrane (SLM) process. The formation of pores and the membrane porosity value can be improved by adding a pore-forming agent in the dope solution during membrane manufacturing. The objective of this study is to investigate the effect of pore-forming additives such as polyethyleneglycol (PEG) 200, PEG 20,000, lithium chloride, Tween-80, and polyvinyl pyrrolidone (PVP 10,000) on the polyethersulfone (PES) membrane properties and their performance in the separation of levulinic acid (LA) using the SLM method. The morphology, contact angle, porosity, and tensile strength of the membrane were evaluated. Among the pore-forming agents tested, PEG 200 emerged as the most effective in inducing a sponge-like structural wall in the PES membrane. It achieved a remarkable porosity level of 87.1%, displaying contact angles of 81.2° and 98° at the top and bottom surfaces, respectively, as well as a high tensile strength of 1032.88 kPa. The membrane achieved the highest extraction of 8.92 g/L LA in the SLM process using a 10 g/L LA aqueous feed solution.